Design and Experiments of A New Internal Cone Type Traveling Wave Ultrasonic Motor - CHEN, Ye; YANG, Junlin; LI, Liang; XIAO, Shihao (Archives of Acoustics, 2023)
In order to simplify the motor structure, to reduce the difficulty of rotor pre-pressure application and to obtain better output performance, a new internal cone type rotating traveling wave ultrasonic motor is proposed. The parametric model of the internal cone type ultrasonic motor was established by the ANSYS finite element software. The ultrasonic motor consists of an internal cone type vibrator and a tapered rotor. The dynamic analysis of the motor vibrator is carried out, and two in-plane third-order bending modes with the same frequency and orthogonality are selected as the working modes. The other advantages of this motor are that pre-pressure can be imposed by the weight of the rotor. The prototype was trial-manufactured and experimentally tested for its vibration characteristics and output performance. When the excitation frequency is 22260.0 Hz, the pre-pressure is 0.1 N and the peak-to-peak excitation voltage is 300 V, the maximum output torque of the prototype is 1.06 N · mm, and the maximum no-load speed can reach 441.2 rpm. The optimal pre-pressure force under different loads is studied, and the influence of the pre-pressure force on the mechanical properties of the ultrasonic motor is analyzed. It is instructive in the practical application of this ultrasonic motor.